Flow‐induced reconfiguration of aquatic plants, including the impact of leaf sheltering. (24th June 2020) - Zhang, Xiaoxia; Nepf, Heidi
Abstract: Many aquatic plants are flexible and bend in response to current. This reconfiguration can reduce the drag on the plant, both by reducing the frontal area and by creating a more streamlined shape. Previous studies have considered how the buoyancy and rigidity of a plant impact the drag reduction. This study additionally considered how reconfiguration impacts the sheltering between leaves on a plant and how this, in turn, impacts the drag on the plant. The posture and drag of single‐stemmed, leaved plants were studied through a combination of laboratory experiments and theoretical modeling using both plastic Rotala bonsai and live Bacopa caroliniana . The laboratory experiments measured drag and posture on individual plants over a range of channel velocity. The theoretical model calculated plant posture and drag based on a force balance that included buoyancy, the restoring force due to stem stiffness, and leaf drag modified to account for sheltering between leaves. Leaf sheltering was characterized by a sheltering coefficient, C s, which is a function of the plant posture, leaf angle, leaf spacing, and leaf width. C s decreased from 1 to a minimum value, C s 0, associated with a fully deflected, horizontal stem posture. Once validated, the model was used to explore a range of leaf configurations, following examples found in real plants. The modeling and experiments revealed conditions for which drag increased with reconfiguration, and also that the drag reached a finite, limiting value for horizontal stem posture. Neither trend has been described in previous reconfiguration models.